H+-activated Na+ influx in the ventricular myocyte couples Ca2+-signalling to intracellular pH - Garciarena, C; Youm, J; Swietach, P; Vaughan-Jones, R (2013)
Acid extrusion on Na+-coupled pH-regulatory proteins (pH-transporters), Na+/H+ exchange (NHE1) and Na+-HCO3- co-transport (NBC), drives Na+ influx into the ventricular myocyte. This H+-activated Na+-influx is acutely up-regulated at pHi<7.2, greatly exceeding Na+-efflux on the Na+/K+ ATPase. It is spatially heterogeneous, due to the co-localisation of NHE1 protein (the dominant pH-transporter) with gap-junctions at intercalated discs. Overall Na+-influx via NBC is considerably lower, but much is co-localised with L-type Ca2+-channels in transverse-tubules. Through a functional coupling with Na+/Ca2+ exchange (NCX), H+-activated Na+-influx increases sarcoplasmic-reticular Ca2+-loading and release during intracellular acidosis. This raises Ca2+-transient amplitude, rescuing it from direct H+-inhibition. Functional coupling is biochemically regulated and linked to membrane receptors, through effects on NHE1 and NBC. It requires adequate cytoplasmic Na+-mobility, as NHE1 and NCX are spatially separated (up to 60μm). The relevant functional NCX activity must be close to dyads, as it exerts no effect on bulk diastolic Ca2+. H+-activated Na+-influx is up-regulated during ischaemia-reperfusion and some forms of maladaptive hypertrophy and heart failure. It is thus an attractive system for therapeutic manipulation. This article is part of a Special Issue entitled "Na+ Regulation in Cardiac Myocytes". © 2013 Elsevier Ltd.